India : Selected Issues. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 1997)
This Selected Issues paper analyzes the medium-term macroeconomic outlook for India. The paper highlights that in the strong adjustment scenario, the joint effect of strong fiscal consolidation and ambitious structural reforms would bring the Indian economy onto a sustainable high growth path, reaching 7 percent around the turn of the century. Although there could be some initial dip in growth, owing to the contractionary effects of fiscal retrenchment, this should be temporary as a strong surge in investment, together with productivity improvements related to structural reforms, should drive an acceleration in growth performance.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet